Statistics from space: a new approach to agricultural production data for Mozambique - Valmonte-Santos, Rowena (CGIAR, 2024)
Crop production statistics are essential for any government, but especially so in Mozambique where agriculture accounts for a quarter of economic production and the livelihoods of 80 percent of the population. The Statistics from Space project, funded by the Government of the Republic of Korea, aims to develop a highly accurate and efficient system to estimate and forecast production of different crops across the country by 2025. The project team worked closely with stakeholders in the Mozambique government to identify their pain points and what would be needed from a new system. They identified challenges such as the diverse cropping systems in Mozambique, the high cost of its current system and timeliness, reliability, and usability. Since the project aligns closely with CGIAR Initiative on Digital Innovation, which focuses on harnessing digital technologies for better decision-making in food, land, and water systems, the Initiative team actively participates in the project to promote synergies in supporting the crop production information system.